A New Quest is Available: seeing, walking and narrating the city - Elita Nuraeny (International Journal of Built Environment and Scientific Research, 2020)
Walking becomes a conversation, of past, present and future, between our body and the city. However, today’s modern hand-held map demands us to look down, disrupting the dialogue between the body and city. Like a modern role-playing game, the map guides us to our quest mark beyond with minimum consideration of the present time. The map makes the quest mark and path visible; yet, the in-between space of our reality is overlooked. Following the idea of a hidden quest mark in our real world, this study explores the lost narrative between our body and the city. The study examined a project named Location + that follows spatial history, experiences and the journey beyond of a hidden church of the Knights Templar in London. The project is filled with instructions to decipher codes, directing people to the church. By using psychogeography, the project Location + approaches a spatial narrative using site writing and creative map-making that is specific to the site. By emphasizing the idea that our journey matters, this project allows a dialogue between the body and city.